Diagnostic pitfalls in neonatal hypertyrosinemia: a case report - Khalid, Karniza; Kamarudzaman, Mohd Fazrul Shafiq; Ahmad Ridzuan, Siti Nurwani; Hamzan, Nurul Izzati; Khalid, Norzahidah; Hassan, Noor Hafizah (Life Sciences, Medicine and Biomedicine, 2023)
Hypertyrosinemia results from abnormality in tyrosine metabolism. Acquired hypertyrosinemia is notably more common than inherited types and typically presents with profile suggestive of secondary aetiology on biochemical testing. Herein, we present an unusual case of a day 16-of-life baby girl who was screened for inborn errors of metabolism (IEM). She presented with jaundice, hypotonia, lethargy and had hepatomegaly on examination. She was treated for sepsis with multiorgan involvement, requiring escalation of intravenous antibiotics and assisted ventilation. Her dried blood spot (DBS) showed moderate elevation of tyrosine (408umol/L, N:10-182) with low Phe:Tyr ratio (0.15mmol/L, N:0.32-3.45). Plasma amino acid showed isolated hypertyrosinemia at 807mmol/L (N:5-167) with mild, non-significant elevations of other liver metabolites. No succinylacetone peak seen with urine organic acids, making the diagnosis of inherited Tyrosinemia type I less likely despite the characteristic findings from DBS, plasma amino acids, and presenting clinical signs. Repeated IEM screening two weeks later revealed a non-diagnostic profile across both DBS and plasma amino acids in light of resolving sepsis and clinical improvement. This case highlights the challenges associated with incompatible biochemical testing in a child with a high index of suspicion for inherited Tyrosinemia. In our case, repeated screening ruled out inherited Tyrosinemia, suggesting the initial picture of hypertyrosinemia to be likely due to liver dysfunction and impaired activity of liver enzymes that are responsible for tyrosine catabolism.